Strategy of Productive Waqf Utilization as a Medium for Food Security in Indonesia: An AHP Approach - Alam, El-Islam Purnama; Juliana; Rosida, Rida (SMART Insight, 2024)
This study aims to determine the problems that exist in the use of waqf as a medium for food security in Indonesia and the priority solutions for the use of productive waqf as a medium for food security in Indonesia in terms of institutional, infrastructure, financial, community and government aspects. this is the Analytical Hierarchy Process (AHP). This study used seven expert respondents representing academics, practitioners and regulators who were asked to assess the problems and solutions for the use of productive waqf as a medium for food security in Indonesia. Based on the opinion of respondents, the biggest problem in the use of productive waqf as a medium for food security in Indonesia is the lack of socialization to the public regarding productive waqf as a medium for food security. The priority solutions in this research are waqf institutions and the government need to collaborate in implementing productive waqf utilization as a medium for food security in Indonesia. Furthermore, in general the aspect that is considered the most problematic is the government aspect, while the priority for solutions is the institutional aspect. Therefore, in the use of productive waqf as a medium for food security in Indonesia, the public needs to increase their understanding of productive waqf as a medium for food security, the government needs to collaborate with waqf institutions and farmer groups as well as waqf institutions need to improve their professionalism.